Reforming Quebec’s Surrogacy Laws - Carsley, Stefanie (Revue générale de droit, 2023)
In October 2021, the Quebec government introduced Bill 2, which proposed significant reforms to Quebec’s surrogacy laws. Quebec’s Minister of Justice emphasized that Bill 2 was intended to better account for the needs and lived realities of Quebec families. He also specified that its surrogacy provisions aimed to prioritize the best interests of children while also protecting surrogates’ rights. This article explores Bill 2’s proposed reforms to Quebec’s surrogacy laws and their implications for surrogates, intended parents, and the children born through these arrangements. I argue that while Bill 2’s proposals would go a long way towards legitimizing and regulating surrogacy arrangements, the bill leaves a series of important questions unanswered and may have effects that run counter to lawmakers’ objectives.The reader should be advised that when this article was being edited and typeset in preparation for publication, the Quebec government re-introduced Bill 2 as « Bill 12 » with some minor modifications to its provisions pertaining to surrogacy. Notably, Bill 12 clarifies that the surrogate will remain the child’s legal parent, and a court will not have discretion to modify the child’s filiation, in the event the surrogate refuses to give up their parental rights following the birth. However, given the similarities between the two bills, this article’s commentary and criticisms remain highly relevant and timely with respect to Bill 12’s proposed reforms to Quebec’s surrogacy laws.